Tecido complexo formativo docente: repercussões dos conhecimentos específicos das áreas nos processos formativos das licenciaturas - Scremin, Greice (2014)
This study is a doctorate s thesis and was performed in the research line 1 formation. Knowledges and profisional development, from Education Post Graduation Program of Federal University of Santa Maria (UFSM), Southern Brazil. This study arises from debates of in CNPq Reseach Group trajectories of Formation GTFORMA, concerned with formative way (personals and professionals) experienced by high level teachers. The general aim of this study was to analyse how specific knowledges repercute in teacher s formative processes. Paradigm of complexity under a case study research and following a qualitative methodology was used to give direction to this study, in which the investigations instruments were official documents (education laws and Licenciate Pedagogical Projects) and narrative interviewing carried out with teachers of UFSM Licenciate courses. Theoretical elements inrolled in this study were aligned to types of knowledges and competencies to be developed by teachers inicial courses, in order to promote a reflexion on veral reality aspects of these courses at UFSM context. Complex interpretative Analysis concept is presented as way of results analysis oriented by complexity principles and Morin s tetragram. It was possible to get to a complex comprehension about formative processes in licenciate courses based on referred analysis. A conceptual term, Teacher Formative Complex Tissue, was coined for getting to this understanding, evidencing that teacher formation needs to be conceived in its complexity at licenciate domains. Tissue is network intertwined by tree complex nets (Specific area net, Teacher s formative net, and Operative-formative net). In this study, interpretation presented has got involved through inter relacional dynamics among tree nets, rebuilded in each interaction. Complexity based on systemic thinking redirect the look to the analyzed reality for making possible the proposition of a new signification and to highlight the importance of rethinking this reality in a more integrated mode. Therephore, the Teacher Formative Complex Tissue is characterized by the incoherence between how teacher formation would be ideally and how efectivelly it is revealed by the study. So, comprehending two important dimensions of this process (official documents and teacher s discourse) in this study, allowed to show the way how the teacher formative process was understood from studied reality.